Landscape and Interaction. The Troodos Archaeological and Environmental Survey Project, Cyprus. Volume 1. Methodology, Analysis and Interpretation - Given, Michael (Council for British Research in the Levant, 2013)
The Troodos Mountain range in central Cyprus is a region of great physical and cultural diversity. The landscapes range from fertile, cultivated plains to narrow, dry valleys and forested mountain regions and this physical topography is overlain by a rich human cultural landscape of farming, mining, industry, settlement, burial and ritual behaviour. Over six field seasons, a team of specialists and fieldwalkers from the Troodos Archaeological and Environmental Survey Project (TAESP) investigated the northern edge of this region and explored the complex and dynamic relationship between landscape and people over 12,000 years. The results of their integrated and interpretative approach are presented here, in the first of two volumes. Beginning with a considered overview of the context, research aims and methodology of the project, Volume 1 provides detailed accounts of the archaeology, material culture, geography and environmental record of the entire survey area. This wealth of information is then bought together to produce a series of chronological and thematic analyses of the interaction between people and landscape in this region of Cyprus from the Prehistoric through to the Modern period.